A possibilidade da aplicação do princípio da insignificância pela autoridade policial - Holanda, Fábio Peixoto (2019)
The principle of trifling or trifling crime is a very important principle in criminal law. Even though there is no legal provision in the Brazilian order, the principle is mostly accepted in doctrine and jurisprudence, away from the material typicality of certain crimes, which although formally described in the criminal wording, do not materially affect the legal good protected by the State. However, such a principle is only applied by the judiciary in criminal procedural matters. Thus, the main objective of the work is to relate the principle of insignificance to the performance of the police chief's activities, so that the other cases that fall under the aforementioned principle are resolved in order to meet the speed and procedural economy.